2020
DOI: 10.1038/s41420-020-00349-0
|View full text |Cite
|
Sign up to set email alerts
|

The caspase-3/GSDME signal pathway as a switch between apoptosis and pyroptosis in cancer

Abstract: Apoptosis has long been recognized as a mechanism that kills the cancer cells by cytotoxic drugs. In recent years, studies have proved that pyroptosis can also shrink tumors and inhibit cells proliferation. Both apoptosis and pyroptosis are caspase-dependent programmed cell death pathways. Cysteinyl aspartate specific proteinase-3 (Caspase-3) is a common key protein in the apoptosis and pyroptosis pathways, and when activated, the expression level of tumor suppressor gene Gasdermin E (GSDME) determines the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
268
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(309 citation statements)
references
References 73 publications
9
268
0
Order By: Relevance
“…Caspase-3 is the most important terminal cleavage enzyme in the process of apoptosis and cleaved-caspase-3 is the activated form of caspase-3 (27). Through western blotting changes in the expression of the apoptosis-related protein cleaved caspase-3 were found in the present study.…”
Section: Discussionsupporting
confidence: 49%
“…Caspase-3 is the most important terminal cleavage enzyme in the process of apoptosis and cleaved-caspase-3 is the activated form of caspase-3 (27). Through western blotting changes in the expression of the apoptosis-related protein cleaved caspase-3 were found in the present study.…”
Section: Discussionsupporting
confidence: 49%
“…Our data showed that GSDME is the major executor responsible for TPL induced pyroptosis in head and neck cancer cells. Until recently, it has been recognized that gasdermins pore forming proteins, not caspases, are determinant of cell death type [ 42 ]. In GSDME-expressing cells, active caspase 3 cleaves GSDME and liberates the pore-forming ability of N-terminus, resulting in cell swelling, membrane rupture, and pyroptotic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies may focus on whether/how PJVK participates in pyroptosis and tumour suppression. CASP3 exists as a non-activated zymogen in its normal state, but upon activation, it produces active executors that cleave structural and regulatory proteins in the nucleus and cytoplasm of cells, thereby regulating cell death, and it is recognized as a marker of apoptosis 30 . In 2017, Wang et al 31 discovered that GSDME was specifically cleaved by chemotherapeutic drug-activated CASP3 to produce a membrane-penetrating GSDME -N fragment, which induced pyroptosis.…”
Section: Discussionmentioning
confidence: 99%